The managers guide to understanding commercial contract negotiation - Adoranti, Frank (London : Lessons Professional Pub., 2006)
The book details what you need to know in Understanding Commercial Contract Negotiation.
Includes index.
rua 23/12/13
Loans
Keywords: Contracts; Negotiation in business; Commercial law; Commercial contract negotiation